MORAL EDUCATION IN THE BOOK TA’LIMUL MUTA’ALLIM THARIQ AL-TA’ALLUM BY SHEIKH BURHANUDDIN AZ-ZARNUJI - Sembiring, Nurhaizan; Adawiyah, Rabiatul; Nurdiani, Nurdiani; Marisa, Siti (Proceeding International Seminar of Islamic Studies, 2023)
This research examines the moral education in the book Ta'limul Muta'allim Thariq Al-Ta'allum by Shaykh Burhanuddin Az-Zarnuji. The focus of the discussion in this research is how moral education is in the book Ta'limul Muta'allim Thariq Al-Ta'allum by Syaikh Burhanuddin Az-Zarnuji. Moral education is the most important thing in education because with moral students it will give birth to a religious person, close to God, and so on. This study uses a type of library research by looking at the text contained in the book written by Syaikh Burhanuddin Az-Zarnuji. The research object is explored in the book 'Ta'limul Muta'allim Thariq Al-Ta'allum' using a content analysis approach. The results of this study indicate that the moral education contained in the book Ta'limul Muta'allim Thariq Al-Ta'allum by Shaykh Burhanuddin Az-Zarnuji has six criteria, namely 1) Intention in learning. 2) Choosing knowledge, teachers and friends. 3) Glorify knowledge and experts. 4) Seriousness in Seeking Knowledge, Beristiqamah, and noble ideals. 5) Tawakkal. 6) Wara'.